2016
DOI: 10.1136/bmjopen-2016-012372
|View full text |Cite
|
Sign up to set email alerts
|

Registry-based analysis of participator representativeness: a source of concern for sickness absence research?

Abstract: ObjectivesSelective participation can bias results in epidemiological surveys. The importance of health status is often suggested as a possible explanation for non-participation but few empirical studies exist. In a population-based study, explicitly focused on sickness absence, health and work, we examined whether a history of high levels of sickness absence was associated with non-participation.DesignThe study is based on data from official sickness absence registers from participants, non-participants and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 39 publications
0
12
0
1
Order By: Relevance
“…An obvious strength of this study is consequently the population-based data we have used, which imply nonselective participation and medically screened cases. Surveys, in contrast, may offer some additional useful information related to health behaviours, health literacy and lifestyles, but they often suffer from problems with non-participation and selective response (Knapstad et al 2016). Sickness allowance receipt may nevertheless be considered a more complex health measure than disability pension.…”
Section: Discussionmentioning
confidence: 99%
“…An obvious strength of this study is consequently the population-based data we have used, which imply nonselective participation and medically screened cases. Surveys, in contrast, may offer some additional useful information related to health behaviours, health literacy and lifestyles, but they often suffer from problems with non-participation and selective response (Knapstad et al 2016). Sickness allowance receipt may nevertheless be considered a more complex health measure than disability pension.…”
Section: Discussionmentioning
confidence: 99%
“…Two postal reminders followed up questionnaire distribution resulting in a final general participation rate of 50% ( n = 4027). Persons born outside Nordic countries had the lowest participation rate (34%), followed by those with the lowest incomes (39%), those in the youngest age group (19–30 years, 41%), men (44%), and those who were unmarried (46%) (Knapstad et al 2016 ). Full details of HAP and an extensive non-response analysis are presented elsewhere (Hensing et al 2011 ; Knapstad et al 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…The T1 questionnaire comprised questions on mental healthcare-seeking at any time in life, mental and physical persistent illness, sociodemographic factors, and an index on mental well-being. A previous analysis of non-participation showed that those born outside the Nordic countries, those with low income, young persons, men, and those who were single were less likely to participate at T1 (31). Previously, several studies have been published based on the T1 questionnaire and the population-based sample, e.g., a recently published study showing gender and education-based differences in unmet need for mental healthcare (24).…”
Section: Study Design and Participantsmentioning
confidence: 99%